The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.4269/ajtmh.13-0624
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Region Between Amino Acids 221 and 266 of Dengue Virus Non-Structural Protein 1 is a Major Epitope Region in Infected Patients

Abstract: Abstract. The immune response to dengue virus (DENV) infection generates high levels of antibodies (Abs) against the DENV non-structural protein 1 (NS1), particularly in cases of secondary infection. Therefore, anti-NS1 Abs may play a role in severe dengue infections, possibly by interacting (directly or indirectly) with host factors or regulating virus production. If it does play a role, NS1 may contain epitopes that mimic those epitopes of host molecules. Previous attempts to map immunogenic regions within D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…However, a recent report showed that NS1-immune polyclonal mouse serum or monoclonal antibodies to NS1, and immunization with NS1 protected mice against DENV-2 in a lethal challenge model [ 23 ], suggesting a role for anti-NS1 antibodies in protection from disease. One of our NS1 epitopes ( Fig 5D–5F , Peak D) was recently identified as a target of human anti-NS1 monoclonal antibodies [ 24 ]. In that report, nine human monoclonal antibodies to NS1 from patients secondarily infected with DENV-2 bound to a common epitope located between amino acids 221–266.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent report showed that NS1-immune polyclonal mouse serum or monoclonal antibodies to NS1, and immunization with NS1 protected mice against DENV-2 in a lethal challenge model [ 23 ], suggesting a role for anti-NS1 antibodies in protection from disease. One of our NS1 epitopes ( Fig 5D–5F , Peak D) was recently identified as a target of human anti-NS1 monoclonal antibodies [ 24 ]. In that report, nine human monoclonal antibodies to NS1 from patients secondarily infected with DENV-2 bound to a common epitope located between amino acids 221–266.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the structure of the DENV2 β‐ladder in complex with the Fab of a neutralizing antibody (22NS1) is consistent with this hexamer arrangement (Figure C), as the 22NS1 epitope is on the hexamer exterior. The 22NS1 epitope overlaps with epitopes mapped for human patient antibodies showing that the hexamer exterior is recognized by secondarily infected dengue patients . Additionally, regions of NS1, which are most varied among the four major dengue serotypes, map almost exclusively to the outer face (Figure ).…”
Section: The Ns1 Hexamer Exposes An Outer Variable Facementioning
confidence: 97%
“… ( a ) Schematic representation of DENV2 ΔNS1. DENV2 ΔNS1 lacks the following antigenic regions from full-length DENV2 NS1 that potentially elicit the production of cross-reactive antibodies: amino acids 116–119 14 , 221–266 15 and 311–330 16 . …”
Section: Figurementioning
confidence: 99%